2018
DOI: 10.2139/ssrn.3306271
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Carbon Emissions: The Road to ‘Hothouse Earth’ is Paved with Good Intentions

Abstract: De-carbonization to restrict future global warming to 1.5 C is technically feasible but may impose a "limit" or "planetary boundary" to economic growth, depending on whether or not human society can decouple growth from emissions. In this paper, we assess the viability of decoupling. First, we develop a prognosis of climate-constrained global growth for 2014-2050 using the transparent Kaya identity. Second, we use the Carbon-Kuznets-Curve framework to assess the effect of economic growth on emissions using mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Additionally, these outcomes are consistent with the preceding literature. In compliance with the previous literature, nations that tend to consolidate their economic growth without considering the efficiency issues suffer from environmental deterioration (For instance, the studies of Lu (2017), Storm and Schröder (2018), Zhang et al (2019) and Jiang et al (2020)). Also, it is consistent with the preceding literature that shifting toward the deployment of clean power sources ameliorates the quality of the environment (For instance, the studies of Katircioglu (2015), Balogh and Jámbor (2017), Dong et al (2017), Bilan et al (2019) and Chandio et al (2021)).…”
Section: Panel Long-run Estimatormentioning
confidence: 62%
See 1 more Smart Citation
“…Additionally, these outcomes are consistent with the preceding literature. In compliance with the previous literature, nations that tend to consolidate their economic growth without considering the efficiency issues suffer from environmental deterioration (For instance, the studies of Lu (2017), Storm and Schröder (2018), Zhang et al (2019) and Jiang et al (2020)). Also, it is consistent with the preceding literature that shifting toward the deployment of clean power sources ameliorates the quality of the environment (For instance, the studies of Katircioglu (2015), Balogh and Jámbor (2017), Dong et al (2017), Bilan et al (2019) and Chandio et al (2021)).…”
Section: Panel Long-run Estimatormentioning
confidence: 62%
“…The results were miscellaneous and indecisive. While some studies found a positive relation between economic progress and environmental deterioration, other studies found a negative or insignificant relation between economic progress and environmental deterioration; as an illustration, the analyses of Azomahou et al (2006), Poudel et al (2009, Saboori et al (2012), Wang (2012), Kasperowicz (2015), Bimonte and Stabile (2017), Lu (2017), Storm and Schröder (2018), Zhang et al (2019), Jiang et al (2020) and Zhang (2021).…”
Section: Economic Progress and Environmental Deteriorationmentioning
confidence: 97%
“…Although it is still too early to make a categorical assessment, these deep changes in Spanish energy policy seem to lay the foundation for a decoupling of emissions and economic activity in the future. However, the general question arises of whether the decarbonization of not just the Spanish economy but also other world economies is sufficient to avoid dangerous climate change and ensure achievable warming of less than 2 • C. Recent publications by climate scientists [72][73][74] are alarming: they suggest that these downward trends in energy and carbon intensity are insufficient to decouple economic growth and CO 2 emissions, and that they are nowhere close to what is needed to meet the longer-term Paris pledges or the recommendations of the IPCC (2018). They warn that even if global emissions are drastically cut down in line with the 66% below 2 • C goal of COP21 (Paris climate agreement of December 2015), a series of self-reinforcing bio-geophysical feedbacks and tipping cascades (like melting sea ice or deforestation) could still contribute to the continued warming of the planet.…”
Section: Discussionmentioning
confidence: 99%
“…We have argued that the firm is a subset of the economy and that the economy needs to be integrated into the finite ecosphere. Storm and Schröder [78] sound the alarm that "business-as-usual" cannot continue-the idea of "green" growth is a myth, and the future has to be different from the past. We see clear indications of social, environmental, interspecies, and intergenerational injustice.…”
Section: Discussionmentioning
confidence: 99%